2002
DOI: 10.1046/j.1463-1326.2002.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a water‐soluble extract of maitake mushroom on circulating glucose/insulin concentrations in KK mice

Abstract: FXM, a natural extract obtained from maitake mushroom, favourably influences glucose/insulin metabolism in insulin-resistant KK mice. The lowering of both circulating glucose and insulin concentrations suggests that FXM works primarily by enhancing peripheral insulin sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 33 publications
1
39
0
Order By: Relevance
“…Inhibition of enzymes involved in the metabolism of carbohydrates such as a-amylase and a-glucosidase, is an important therapeutic approach for reducing postprandial hyperglycemia . aAmylase found in the saliva and pancreatic juice, catalyses the hydrolysis of polysaccharides (such as starch) to disaccharides (like maltose and sucrose) (Manohar et al, 2002). Though ethanol extract of D. basuticus displayed the strongest inhibition of a-amylase (IC 50 34.02 mg/mL) and is more potent than the standard (acarbose) (IC 50 65.37 mg/mL) (Table 2), it may be unsuitable for usage as an antidiabetic agent.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of enzymes involved in the metabolism of carbohydrates such as a-amylase and a-glucosidase, is an important therapeutic approach for reducing postprandial hyperglycemia . aAmylase found in the saliva and pancreatic juice, catalyses the hydrolysis of polysaccharides (such as starch) to disaccharides (like maltose and sucrose) (Manohar et al, 2002). Though ethanol extract of D. basuticus displayed the strongest inhibition of a-amylase (IC 50 34.02 mg/mL) and is more potent than the standard (acarbose) (IC 50 65.37 mg/mL) (Table 2), it may be unsuitable for usage as an antidiabetic agent.…”
Section: Discussionmentioning
confidence: 99%
“…Regular consumption of GF is believed to enhance immune systems, to lower blood glucose, and to improve the spleen, stomach, and nerve functions. Extracts and polysaccharides of liquid cultured GF have been shown to possess immunomodulatory (Kodama et al, 2004), anticarcinogenic (Kodama et al, 2002), antihyperglycemic (Horio & Ohtsuru, 2001;Kubo et al, 1994;Manohar et al, 2002), antihypertensive , antihyperlipidemic (Fukushima et al, 2001), and antioxidative (Zhang et al, 2002) activities. a-Glucan of GF fruiting bodies was demonstrated to have antidiabetic activity in type 2 diabetic animals (Lei et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Nutritionally, mushrooms provide key nutrients and bioactive components such as high quality protein, some vitamins including riboXavin, niacin, and folates, minerals (potassium, phosphorus, magnesium, zinc, copper, and selenium), unsaturated fatty acids, and Wber (Chang, 1996;Mattila et al, 2001). Several studies have indicated that consumption of mushrooms or isolated bioactive constituent contained in mushrooms may promote health by improving immunity (Sia & Candish, 1999), lowering blood cholesterol and lipid (Cheng, Hou, & Lu, 2002), reducing blood pressure (Kabir, Yamguchi, & Kimura, 1987), attenuating blood glucose (Manohar, Talpur, Echard, Lieberman, & Preuss, 2002), acting as a chemoprotectant (Grube, Eng, Kao, Kwan, & Chen, 2001), and having antibiotic activity (Van Nevel, Decuypere, Dierick, & Molly, 2003).…”
Section: Introductionmentioning
confidence: 99%